AN EMPIRICAL APPROACH TO DESIGN A PIFA ANTENNA - M. Sharif, Sami; D. Abdalla, Iman (University of Khartoum Engineering Journal, 2022)
Abstract: A parametric study is performed on a Planar Inverted F Antenna (PIFA) that operates at the frequency of 900 MHz The effect of the variation of the parameters on the bandwidth (BW) is analyzed. The study is performed using the Finite Element Method (FEM) numerical technique and the High Frequency Structural Simulator (HFSS) software. Regression analysis is applied on the data obtained from the simulation to present a mathematical model that estimates the fractional bandwidth FBW. An empirical equation that predicts the FBW of the PIFA is introduced. The equation uses the effective design parameters; substrate material thickness and ground plane dimensions as predictors. A comparison between the results calculated by the equation and the results obtained via simulation is carried out for validation purposes. The results are found to be very close except for the values corresponding to substrate thicknesses above 6mm. Moreover, a second simulator using a different numerical technique is used for further verification. A PIFA that operates at the 900 MHz frequency is fabricated. The results obtained from the physical measurement are compared with the results calculated by the empirical equation and the results obtained from the simulation. Close compatibility is observed.